The Influence of Religiosity and Rational Motivation on Interest in Saving at BMT UGT Nusantara - Dania, Reza Rohma; Supandi, Ach Faqih; Afiq, Ahmad Zubadul (Wealth: Journal of Islamic Banking and Finance, 2023)
This study aims to analyze the effect of religiosity and rational motivation on the interest in saving at BMT UGT Nusantara capem Kaliwates. This study uses quantitative research with data collection techniques through observation, questionnaires, documentation. Data collection uses statistical data analysis research instruments with the aim of testing the hypotheses that have been set. The population in this study were customers of BMT UGT Nusantara Capem Kaliwates. The sampling technique used is probability sampling, which is a sampling technique that provides equal opportunities for all members of the population to be selected as samples. Then this sampling technique was combined with the cluster random sampling technique, which is a technique for selecting a sample from small groups of units with a total sample taken of 96 customers at BMT UGT Nusantara Capem Kaliwates. In processing the data the researcher used the SPSS 25.0 program. Researchers use multiple linear regression analysis. Based on the results of the research and the results of data analysis and discussion of the results of the data, it was concluded that religiosity has a significant effect on the intention to save at BMT UGT Nusantara Capem Kaliwates with a tcount of 6.823 > ttable of 1.986 with a sig value of 0.001 <0.05. Rational motivation has a significant effect on the Interest in Saving at BMT UGT Nusantara capem Kaliwates with a tcount of 5.067 > ttable of 1.986 with a sig value of 0.001 <0.05. Meanwhile, based on the results of the Anova test or F test, it is known that the significant value for the influence of Religiosity and Rational Motivation simultaneously on the Intention to Save the community at BMT UGT Nusantara capem Kaliwates is 0.001 <0.05 and fcount value is 147.531 > ftable 3.094, thus these results give the meaning that the variable Religiosity (X1) and Rational Motivation (X2) simultaneously have a significant effect on the Interest in Saving (Y). H1 is accepted and H0 is rejected.